ANDERSON TAXONOMY-BASED INTENSIVE TEST EVALUATION TOOL FOR SENIOR HIGH SCHOOL - Abduh Khairani Nurul (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
Evaluation is one of the components covered in the education system and listening is one of the language skills that needs maximum attention. The purpose of this article is to describe the form of listening skills tests based on Anderson's taxonomy theory. The categories in Anderson's cognitive process dimensions are divided into six categories which are marked with the code C1-C6, namely remember (C1), understand (C2), apply (C3), analyze (C4), evaluate (C5), and create (C6) The results of the test instruments made were intended for class X high school students in the form of multiple choice tests in the amount of twenty questions. The scoring system used is an objective test scoring system.